PENERAPAN ESTETIKA PENATAAN RUANG PERPUSTAKAAN ANAK - Salma Zahra Fauziyah; Heri Hidayat (Al Athfal : Jurnal Kajian Perkembangan Anak dan Manajemen Pendidikan Usia Dini, 2021)
Indonesia is a country with low interest in reading, one of the reasons is the lack of adequate facilities that help in growing interest in reading in the community, especially in children. One of the efforts that can be done in fostering interest in reading is to familiarize children from an early age to enjoy reading apart from that, the provision of supporting facilities and facilities in the form of a children's library. Organizing a children's library room certainly needs to meet the criteria for a good arrangement, the application of aesthetic values, also in accordance with the characteristics of the child. The purpose of this study was to find out more about the application of aesthetics in the arrangement of children's library spaces. The method used is a descriptive method with literature study, data collection with this method is carried out in the literature, by searching on the internet in the form of books, journals, articles, also with pictures, videos, and other media that support this research. The arrangement of the children's library space needs to pay attention to the principles and elements of the arrangement of the library space, as well as the aesthetic principle, where it can support beauty, so that the library can be comfortable and beautiful to look at.